Transições de fase induzidas por altas pressões no molibdato de ítrio - Dias, Abraão Cefas Torres (2011)
In this work we investigate the vibrational properties of anhydrous and hydrated yttrium molibdate as a function of hydrostatic high pressures. An analysis of vibrational modes suggests that this material experiences a phase transformation from orthorhombic to a lower symmetry (probably monoclinic) phase about 0.3 GPa, and to a high disordered phase above 2.4 GPa. The structural transition to the high pressure disordered phase is not reversible and suggests the onset of a pressure induced amorphization process. The vibrational modes dependence on pressure is discussed considering lattice dinamics calculations.